Using piezoelectric sensor and actuator for ultrasonic assisted system. (18th November 2017) - Ting, Yung; Tang, J.-H.; Chen, J.-C.; Yu, C.-H.
ABSTRACT: An ultrasonic assisted system mainly consists of the transducer and the match-fitting cutter is designed to provide miniature vibration amplitude. In the transducer, a set of piezoelectric ceramics is used as actuator in charge of generating large enough vibration amplitude, which will be immediately measured by the neighboring sensor also made by piezoelectric ceramics. Since the driving frequency is easily affected by the changing working environment, variation of the vibration output is detected in time by the PZT sensor to support the feedback autoresonance control purpose. However, measurement on the transducer is not equivalent to that on the cutter. Further investigation on the measured output of the cutter in comparison with that of the transducer is carried out. It is found that there exists a reasonable and predictable relation between them. ANSYS is used for modal and harmonic analysis. The estimated resonance frequency and vibration amplitude are approximate to the experimental results, which verifies the accuracy of the proposed measurement method.